Digital Media Literacy in Scholarly Discourse: A Bibliometric Analysis of Scopus-Indexed Publications - Ahmad Riyadh Umar Bahlamar (Program Studi Ilmu Perpustakaan UIN Alauddin, 2024)
This study employed bibliometric analysis to examine research developments and identify emerging topics in digital media literacy, utilizing data from the Scopus database spanning 2018–2024. The analysis aims to uncover trends, highlight key contributors, and explore gaps in the existing literature. Data were analyzed using VOSviewer and Biblioshiny software to map research productivity, citation patterns, and collaborative networks. The study revealed a steady annual increase in publications on digital media literacy, with the highest average citation rate observed in 2020. The United States leads in both publication output (1,547 articles) and citation impact (5,422 citations), followed by Spain, Indonesia, and Australia. Prominent contributors in the field include Garcia-Ruiz, Rosa; Romero-Rodriguez, Luis M.; Aguaded, Ignacio; and Perez-Rodriguez, Amor, who have significantly shaped collaborative networks. Keyword analysis identifies recurring themes such as “digital literacy,” “COVID-19,” and related concepts, reflecting the field’s responsiveness to global challenges and its evolving focus. This study underscores the increasing scholarly attention to digital media literacy and highlights opportunities for future research, including addressing interdisciplinary gaps and fostering international collaboration to further advance the field.